Bone density and depressive disorder: a meta‐analysis. Issue 8 (18th May 2016) - Schweiger, Julietta Ursula; Schweiger, Ulrich; Hüppe, Michael; Kahl, Kai G.; Greggersen, Wiebke; Fassbinder, Eva
Abstract: Background: The aim of this study was to evaluate the evidence of low bone mineral density (BMD) in depression. Low BMD is a major risk factor for osteoporotic fractures and frailty. Methods: The searched database was Pubmed, Meta‐analysis included human studies in men and women fulfilling the following criteria: (1) assessment of BMD in the lumbar spine, the femur or the total hip; (2) comparison of BMD between depressed individuals and the healthy control group; (3) measurement of BMD using dual‐energy X‐ray absorptiometry (DEXA); and (4) data on the mean, standard deviation, or standard error of BMD. Results: Twenty‐one studies were identified, encompassing 1842 depressed and 17, 401 nondepressed individuals. Significant negative composite weighted mean effect sizes were identified for the lumbar spine ( d  = −0.15, 95%CL −0.22 to −0.08), femur ( d  = −0.34, 95%CL −0.64 to −0.05), and total hip ( d  = −0.14, 95%CL −0.23 to −0.05) indicating low BMD in depression. Examining men and women shows low bone density in the lumbar spine and femur in women and low bone density in the hip in men. The differences between men and women with MDD and the comparison group tended to be higher when examined by expert interviewers. Low bone density was found in all age groups. Conclusions: Bone mineral density is reduced in patients with depressive disorders. The studies provide little evidence for potential relevant mediating factors. Abstract : Bone mineral density is reduced in patients with depressive disorders at the lumbar spine, femur, and hip. Studies up to now provide little evidence for mediating factors.